Sistem Informasi Persediaan Stok Benih Tanaman Menggunakan Teknologi Barcode dalam Studi Kasus Kantor BPTH Wilayah II - Nadya Febrianti; Faridah Yusuf; Izmy Alwiah Musdar (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Plant seed stock management is a crucial aspect in supporting the success of forest rehabilitation programs and environmental conservation efforts. Guaranteed seed availability, both in terms of quantity and quality, is a key factor in supporting sustainable reforestation activities. However, the reality on the ground shows that the seed stock management process at the Forest Plant Seed Agency (BPTH) Region II Office is still carried out manually. Recording is carried out conventionally, from recording incoming and outgoing seeds, through data collection, to distribution. This manual system has proven inefficient due to the time required to search for data and the potential for stock calculation errors. To address these issues, this study aims to design and build a web-based plant seed stock information system equipped with barcode technology. The use of barcode technology is expected to improve recording effectiveness, accelerate tracking processes, and minimize errors in stock data collection. This study used quantitative methods, collecting data through questionnaires and interviews with relevant parties. Furthermore, the system was tested using User Acceptance Testing (UAT) to measure user acceptance and usability. The research results show that the designed information system significantly improves the efficiency of the seed stock data update process. The user acceptance test (UAT) yielded a score of 84.84%, categorized as highly effective. Therefore, the system is deemed suitable for implementation in BPTH Region II as a more modern, faster, and more accurate seed inventory management solution.